2021
DOI: 10.3390/su13179994
|View full text |Cite
|
Sign up to set email alerts
|

Actual and Perceived Motor Competence in Relation to Body Mass Index in Primary School-Aged Children: A Systematic Review

Abstract: Unhealthy-weight status may represent a precursor of poor actual (AMC) (i.e., process- and product-oriented) and perceived (PMC) motor competence. AMC and PMC represent key elements favoring long-term commitment in sports and day-to-day life physical activity. In fact, the development of AMC and PMC during the primary school years could help to counteract weight-related negative effects (i.e., overweight or obesity) that are responsible for sedentary or unhealthy behavior across the life span. Therefore, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…In most cases, such correlations were presented for children who were active in sports and confirmed the natural influence of the seasons [ 39 , 40 ]. In general, overweight children tend to perform less well and are more likely to be inactive [ 41 ]. Chee et al showed, in 243 Malaysian preschool-aged children, that body surface area exposed to sunlight, including outdoor exercise, solar index, and fat mass, were significant predictors of 25(OH)D concentration in this population [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, such correlations were presented for children who were active in sports and confirmed the natural influence of the seasons [ 39 , 40 ]. In general, overweight children tend to perform less well and are more likely to be inactive [ 41 ]. Chee et al showed, in 243 Malaysian preschool-aged children, that body surface area exposed to sunlight, including outdoor exercise, solar index, and fat mass, were significant predictors of 25(OH)D concentration in this population [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Non-communicable Disease Risk Factor Collaboration (NCD RisC) meta-analysis estimated that there are around 213 million overweight and 124 million children and adolescents (age [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] with obesity in the World [1]. The prevalence of overweight among children and adolescents aged 5-19 has risen dramatically from just 4% in 1975 to over 18% (18% of girls and 19% of boys) in 2016 [1].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, being overweight in childhood may affect motor competence for physical activities, as well as for professional activities in later life. Therefore, early involvement in sports activities may be important to counteract weight-related negative effects, through the improvement of movement skills and cognitive functions [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, before this step, further research is required to understand how OCL may acutely impact players' performance in game-based scenarios. This seems especially important if it is considered the lower levels of perceived motor competence by non-experienced players [26]. In fact, using perceptual-motor activities may contribute to improve the perceived motor competence, and consequently, contributing towards a better quality of life [26].…”
Section: Introductionmentioning
confidence: 99%